Potential of Hexadecanoic Acid as Antimicrobials in Bacteria and Fungi that Cause Decay in Mustard Greens Brassica juncea L. - Nadhila Idris (International Journal of Applied Biology, 2022)
Mustard greens Brassica juncea L. one of vegetable that is very easily damaged by microorganisms known as soft rot disease. This causes a decrease in the quality of green mustard so that it cannot last long. A study entitled “The Potential of Hexadecanoic Acid Compounds as Antimicrobials in Bacteria and Fungi that Cause Decay in Mustard Greens Brassica juncea L.". This research aims to specify the effect of hexadecanoic acid compounds in inhibiting the growth of bacteria and fungi that cause decay in mustard greens. An inhibition test was carried out on Xanthomonas campestris bacteria and Fusarium oxysporum fungus using 10%, 20%, and 40% hexadecanoic acid test compounds. The results obtained showed that 10%, 20%, and 40% hexadecanoic acid extracts were able to inhibit the growth of Xanthomonas campestris bacteria and the fungus Fusarium oxysporum. Hexadecanoic acid compounds are bacteriostatic in Xanthomonas campestris and fungi Fusarium oxysporum are fungistatic.